Розвиток правового забезпечення дигіталізації виконавчої влади в Україні 2014-2022 рр.: теоретико-правовий аналіз - Наджафлі, Е.; Nadzhafli, E. (Наше право. - 2024. - № 1. - С. 386-393, 2024)
Стаття присвячена аналізові сучасного етапу дигіталізації виконавчої влади України в контексті модернізації державного управління й реалізації заходів з адміністративної реформи в сучасній Україні, у розрізі упровадження концепції електронного урядування. У цей час завершився процес запровадження єдиної загальнодержавної системи електронного документообігу в органах виконавчої влади; створення єдиної системи публічних електронних реєстрів, розпорядниками яких є органи виконавчої влади; забезпечення надання органами виконавчоїї влади адміністративних послуг в електронній формі громадянам і суб’єктам господарювання в різних сферах суспільного життя; інституціалізація електронної адміністративної процедури та електронної нормотворчості органів виконавчої влади; були створені правові умови для електронної участі громадян, їх об’єднань і суб’єктів господарювання у процесі підготовки державних рішень органами виконавчої влади тощо. Доведено, що упродовж цього етапу дигіталізація виконавчої влади зберігає високу динаміку та з плином часу охоплює своїм регулятивним впливом дедалі ширше коло суспільних відносин.

The article is devoted to legal analysis of the current stage of digitization of the executive power of Ukraine in the context of the modernization of state administration and the implementation of administrative reform measures in modern Ukraine, in the context of the introduction of the concept of electronic governance. It is shown that the newest stage is the stage of systemic digitalization of executive power in the context of digitalization of society, the state, and the economy, according to the paradigms of peoplecenteredness, development of democratic institutions, European integration, and digital transformation, chronologically beginning in 2014 and continuing until now. At this time, the process of introducing a unified state-wide system of electronic document management in executive bodies was completed; creation of a unified system of public electronic registers managed by executive authorities; ensuring the provision of administrative services by executive authorities in electronic form to citizens and business entities in various spheres of social life; institutionalization of electronic administrative procedure and electronic rule-making of executive authorities; legal conditions were created for the electronic participation of citizens, their associations and business entities in the process of preparing state decisions by executive authorities, etc. It has been proven that during this stage, the digitalization of the executive power maintains high dynamics and over time covers an increasingly wider range of social relations with its regulatory influence. It significantly changes the paradigm of the existence of the executive power in the aspect of turning to human-centeredness as such a legal practice of the activities of the executive power bodies, to what extent the coverage of digitalization develops and expands the catalog of rights of citizens in the field of communication with the executive power bodies, as well as the legal possibilities of their implementation in a modern electronic format.

Статья посвящена анализу современного этапа дигитализации исполнительной власти Украины в контексте модернизации государственного управления и реализации мер по административной реформе в современной Украине, в разрезе внедрения концепции электронного управления.
Keywords: дигіталізація; система виконавчої влади; органи виконавчої влади; державне управління; адміністративна реформа; digitalization; system of executive power; bodies of executive power; public administration; administrative reform; дигитализация; система исполнительной власти; органы исполнительной власти; государственное управление; административная реформа